The Role Of The Sukabumi City Tripartite Cooperation Institution For The 2022-2025 Term In Resolving Industrial Relations Disputes - Alyarizki, Ajeng Suci; Mulyadi, Andi; Amirulloh, M Rijal (International Journal of Education, Information Technology, and Others, 2024)
This study aims to analyze the role of the Sukabumi City Tripartite Cooperation Institution for the 2022-2025 service period in resolving industrial relations disputes. The problem of industrial relations disputes in Sukabumi City continues to occur from 2021 to 2023, which has the potential to reduce labor confidence in the company. This research uses a qualitative method with a descriptive approach, collecting data through observation, interviews, and documentation. The results showed that the Tripartite Cooperation Institution plays a role in formulating policies, being a communication tool, strategy, and dispute resolution in industrial relations. However, the effectiveness of this institution is constrained by the lack of coordination between related parties and uneven participation in the settlement process. In conclusion, although the Tripartite Cooperation Institution plays an important role in maintaining industrial relations stability, there is still room for improvement in terms of strategy and communication to achieve more optimal results.